WATER BATH SONICATOR AS AN ECO-FRIENDLY TECHNIQUE FOR SYNTHESIS OF NEW DIHYDRAZIDE HYDRAZONE DERIVATIVES - AL-LAHIBI, AMMAR MAZIN ABDULLAH; AL-HADEDI, AZZAM AHMED MOHAMMED; AL-HAJJAR, MOATH ABDULLAH NAJIM (Journal of Duhok University, 2023)
In this study, the synthesis of a few dihydrazide hydrazone molecules (A1–A6) employing a green chemistry strategy was accomplished successfully using straightforward, environmentally friendly methods. In a water bath sonicator, succinic dihydrazide (1 equivalent) and a variety of aldehydes (2 equivalents) were combined to quickly and efficiently synthesize the necessary compounds. The synthesized compounds were looked into and verified using IR, 1H-NMR, and 13C-NMR as well as physical properties. It’s interesting to note that NMR data revealed that each produced chemical had many tautomeric isomers through proton transfer, as well as asymmetric structures. Actually, it is anticipated that the resultant compounds will have a great ability to form complexes with heavy metals, making them valuable in a variety of significant domains